Antimicrobial susceptibility of chili extracts against foodborne pathogens and food related bacteria - Thavornsawadi, K.; Ngamlerst, C.; Phakawan, J.; Tepsorn, R. (International Journal of Agricultural Technology, 2021)
The comparative evaluation of antimicrobial activities of chili crude extract was inestigated using aqueous, 50 and 95% (v/v) ethanol. Chili crude extract demonstrated inhibitory potential against 25 tested microorganisms, including foodborne pathogens and food-related bacteria. The chili crude extract using 95% (v/v) ethanol solution had the highest efficacy on microbial inhibition. Time-killing analysis were evaluated. The lowest MIC and MBC of 25 bacterial stains was found in Vibrio cholerae DMST 9700 at 0.5% and 1.0% respectively. According to the Time killing analysis, the results indicated that the completed destruction phenomenon of bacterial mixture was detected at the concentration of more than 10.0%w/v of chili crude extract.